Faktor Yang Mempengaruhi Penilaian Mutu Pelayanan Kebidanan Bagi Pasien Rawat Inap Kebidanan Di RSUD Dr. Drajat Prawiranegara Serang-Banten Tahun 2015 - Liana Muslihah; Nuria Fitri Adista (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Knowledge of the rights and obligations of the community as consumers to receive professional healthcare services is increasing. Therefore, companies in the service sector continue to improve the quality of services for consumers with the aim of creating user satisfaction. One of them is the Regional General Hospital, which becomes the choice for the wider community because it is cheaper compared to private hospitals. Even though sometimes the service is less satisfactory. This research was conducted in April - May 2015 in the Obstetrics Inpatient Room of Wijaya Kusuma Hospital, Dr. Drajat Prawiranegara Regional General Hospital, Serang. This research is a quantitative descriptive study using a cross-sectional approach with accidental sampling technique that meets the inclusion criteria. The results of this study are from 155 respondents, 54.8% assessed the quality of obstetric services in the obstetrics inpatient ward of RS Dr. Drajat Prawiranegara as not good. Descriptive analysis results show respondents are aged between 20-30 years (55.5%), have a low level of education (54.8%), do not work (56.1%), use costs from government/private insurance (81.9%), and have a new patient status (69.7%). The conclusion of this study is that there are significant factors related to the assessment of the quality of obstetric services, namely the source of cost (p=0.031), while factors that are not related are age (p=0.219), education (p=1.000), occupation (p=0.218), and patient status (p=0.25). There is one factor that has the most influence on the assessment of the quality of obstetric services based on multivariate analysis, namely the source of cost with an exp (B) value of 0.339.